Do People Believe They Are Less Predictable Than Others? Three Replications of Pronin and Kugler’s (2010) Experiment 1 - Subramanya Prasad Chandrashekar; Stephanie Permut; Hallgeir Sjåstad; Chelsea (Chi Wing) Lo; Yong Jun Kueh; Emily Sihui Zhong; Kai Hin Wan; Kai Yi Kelly Choy; Man Chung Wong; Stanley Wei Jian Hugh; Khan Tahira; Bo Ley Cheng; et al. (International Review of Social Psychology)
Pronin and Kugler (2010) proposed that people believe they have more free will than others. In their Experiment 1 they showed that US students evaluated their own decisions and life events as less predictable than similar decisions and life events of close others, presumably suggesting higher free will attributions. We conducted three pre-registered replications of this study, one with a Hong Kong undergraduate sample (N = 47) and two online samples from the USA (MTurk using CloudResearch: N = 126, Prolific: N = 858) (overall N = 1031). In Studies 1a and 1b that mirrored the target article’s mixed design (self-other between, past-future within), we found support for the original findings with weaker effects. In Study 2 we contrasted between-subject versus within-subject designs in a single data collection. We successfully replicated the effects with the between-subject design, whereas we failed to find support for the effect using the within-subjects design. This suggests support for the phenomenon in single evaluation mode assessing either the self or the other, but that people correct for the self-other asymmetry in perceived predictability when the judgment is made in joint evaluations mode. Materials, data, and code are available on: https://osf.io/ykmqp/. Open peer review: https://osf.io/d47kj.